Oxidação de CO sobre catalisadores de Co e/ou Mn modificados com Mo e suportados em SBA-15 – Efeito do método de preparação e da presença de vapor de água e dióxido de enxofre na atividade catalítica - Lima, Thiago de Melo (Universidade Federal de São Carlos, 2016)
The increasing demand for oil and oil derived products contributed to the alarming increase in the gaseous pollutants emissions in general and mainly contributed to the increase in carbon monoxide (CO) emissions in the worldwide. Besides being delivered on fossil fuels burning processes, a large amount of CO is also generated during the oil refining process, especially in the fluid catalytic cracking unit (FCC). In order to reduce the costs associated to the CO oxidation catalysts many efforts have been devoted to substitution of noble metals by non-noble transition metals, such as cobalt oxides and manganese oxides. However, the biggest challenge for this replacement is to keep the activity of these catalysts in the presence of interfering agents, such as SO2 and H2O, which might deactivate the catalysts or even inhibit the CO oxidation reaction. In this context, the aim of this study is to evaluate the activity of cobalt and/or manganese catalysts, promoted or not by molybdenum and supported on mesoporous molecular sieve type SBA-15 in the CO oxidation reaction in the presence of SO2 (450 ppm) and H2O (10% V/V). These catalysts were prepared by three different methods: (i) impregnation, (ii) deposition-precipitation using microwave and (iii) one-pot. It is noteworthy that the catalysts prepared by the methods of deposition-precipitation and one-pot represents a major breakthrough regarding to green synthesis methods, since they allowed representative savings of energy and water. It was found that the one-pot and deposition-precipitation methods yielded catalysts with high dispersion of the active phase and quite active in CO oxidation reaction. Furthermore, analysis of XRD, Raman, EPR, UV-Vis, XPS and H2-TPR revealed that the one-pot method yielded better dispersion of the molybdenum species over the SBA-15 support, which provided excellent resistance to the cobalt and/or manganese catalysts to SO2 and H2O poisoning. Moreover, the catalysts promoted by molybdenum and prepared by the deposition-precipitation method were composed by cobalt or manganese molybdates, as indicated by XRD, Raman, UV-Vis and XPS techniques, which are less active in the CO oxidation reaction. The catalysts promoted by molybdenum and prepared by the impregnation method possessed a smaller dispersion of the promoter, with the formation of molybdenum oxide, and thus reducing the resistance of these catalysts in the presence of the interfering agents.
Keywords: Cobalto; Manganês; Molibdênio; Oxidação; Monóxido de carbono; Dióxido de enxofre; Cobalt; Manganese; Molybdenum; Oxidation; Carbon monoxide; Sulfur dioxide; ENGENHARIAS::ENGENHARIA QUIMICA